S-Tune: SOT-MTJ manufacturing parameters tuning for securing the next generation of computing - Chowdhury, Muhtasim Alam; Hossain, Mousam; Mastrangelo, Christopher; DeMara, Ronald F.; Salehi, Soheil (Frontiers in Electronics, 2024)
Hardware-based acceleration approaches for Machine Learning (ML) workloads have been embracing the significant potential of post-CMOS switching devices to attain reduced footprint and/or energy-efficient execution relative to transistor-based GPU and/or TPU-based accelerator architectures. Meanwhile, the promulgation of fabless IC chip manufacturing paradigms has heightened the hardware security concerns inherent in such approaches. Namely, unauthorized access to various supply chain stages may expose significant vulnerabilities resulting in malfunctions including subtle adversarial outcomes via the malicious generation of differentially-corrupted outputs. Whereas the Spin-Orbit Torque Magnetic Tunnel Junction (SOT-MTJ) is a leading spintronic device for use in ML accelerators, as well as holding security tokens, their manufacturingonly security exposures are identified and evaluated herein. Results indicate a novel vulnerability profile whereby an adversary without access to the circuit netlist could differentially-influence the machine learning application's behavior. Specifically, ML recognition outputs can be significantly swayed via a global modification of oxide thickness (Tox) resulting in bit-flips of the weights in the crossbar array, thus corrupting the recognition of selected digits in MNIST dataset differentially creating an opportunity for an adversary. With just 0.05% of bits in crossbar having a flipped resistance state, digits '4' and '5' show the highest overall error rates, and digit '9' exhibit the lowest impact, with recognition accuracy of digits '2', '3', and '8' unaffected by changing the oxide thickness of SOT-MTJs uniformly from 0.75 nm to 1.2 nm without modifying the netlist nor even having access to the circuit design itself. Exposures and mitigation approaches to such novel and potentially damaging manufacturing-side intrusions are identified, postulated, and quantitatively assessed.